PENDEKATAN COLLABORATIVE GOVERNANCE DALAM PENGELOLAAN SAMPAH PADA BANK SAMPAH KECAMATAN MANGGALA - Ikram, Mulkhaeri ikram (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2020)
Garbage is a complex problem that every big city has. The waste problem is acommon problem that requires efforts and efforts from the community, privatesector actors and the government to handle it. Therefore, one of the efforts of the Makassar City Government in handling waste is the establishment of a WasteBank in each region with a Central Waste Bank under the Makassar CityEnvironmental Service. Collaborative Governance was born due to limitedresources and government finances in the continuity of the management of theWaste Bank which is now in every District of Makassar City. One of them is theManggala Sector Waste Bank under the leadership of the Manggala DistrictGovernment which is now collaborating with PT. Pegadaian since 2019. Theinscription of cooperation between Manggala District and PT. Pegadaian wasinaugurated in 2019 and inaugurated by the deputy mayor of Makassar with thetheme “The Gade Clean & Gold Waste Sorting Program Saving Gold PT.Pawnshops and Manggala District